EVALUASI SETTING RELAI JARAK (DISTANCE RELAY) PADA SALURAN UDARA TEGANGAN TINGGI (SUTT)150 kV ANTARA GARDU INDUK SIDERA-GARDU INDUK TIPO - Martho Pamula; Sangbua Dinsol Pirade; Yulius S. Pirade; Nurhani Amin (Foristek, 2019)
Abstract-Overhead line high voltage (SUTT) or commonly called a transmission network or transmission line has very important role in the process of distribution of electrical from power plants to load centers continuously. However, overhead line is one component in the system which is often fault. To avoid damages and greater losses, it has used the distance which is as the primary protection in securing the transmission network or transmission line. In this research, it discussed about one phase-neutral short circuit that happens on line transmission connected to Sidera-Tipo substation by calculating the current fault andoperating time of distance relay using the software of ETAP (electric transientandanalysis program) 12.6.0.